Study of laser interactions with quantum particles / Tan Kai Shuen - Tan, Kai Shuen (2013)
In this research, we consider the interaction between an atomic or molecular quantum system (QS) and a metallic nanoparticle (MP). We modelled QS by a three-level lambda system. Under the probe field and control field, the QS become transparent to incident light within a narrow spectrum of frequency, a phenomena known as electro- magnetically induced transparency (EIT). The quantum coherence of the QS under EIT and the strong exciton-plasmon coupling between the QS and MP are dependant on each other. The analytical expressions for the interaction of QS and MP are derived using two methods. First, the QS-MP system is considered as a one-dimensional problem. The ex- pressions derived using this method is not general, however, they provide a simple and more intuitive understanding of the interaction. The second method employed to derive the analytical expressions is by using a vectorial description. Using this model, the exact and general expressions describing the QS-MP system are derived. The density matrix of the QS-MP system was used to obtain numerical results for the dielectric function of QS and MP. The effect of field detuning, distance between the QS and MP, laser field direction and polarization on the dielectric functions are investigated.